Effect of Different Levels of Urea Super Granule and Prilled Urea on the Crop Quality, Nutrient Uptake and Soil Nutrient Status of Broccoli (The Agriculturists, 2018)
A field experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during the period 2010-2011 to assess the effect of urea super granule (USG) and prilled urea (PU) on the quality attributes (Compactness coefficient, Vitamin C, β-carotene and chlorophyll contents) of broccoli, to assess the comparative performance of USG and PU on nutrient uptake and uptake efficiency of broccoli plant, to assess the effect of different forms and levels of urea N on the post harvest soil nutrient status of broccoli field and to select the better doses of USG and PU for quality broccoli production in Shallow Red-Brown Terrace Soil under Madhupur Tract (AEZ-28). The experiment was laid out in a randomized complete block design with three replications having 17 treatments constituted with different levels of urea super granule (USG) and prilled urea (PU) as- T1: N-control,  T2: PU-N80, T3: PU-N100, T4: PU-N120, T5: PU-N140, T6: PU-N160, T7: PU-N180, T8: PU-N200, T9: PU-N220, T10: USG-N80, T11: USG-N100,  T12: USG-N120, T13: USG-N140, T14: USG-N160, T15: USG-N180, T16: USG-N200, T17 and USG-N220 kg ha-1. Results revealed that the comparative performance of USG in relation to head quality (compactness coefficient, ascorbic acid, β-carotene and chlorophyll content), nutrient (NPKS) uptake and N uptake efficiency was found better as compared to PU. The compactness coefficient, β-carotene and chlorophyll contents were increased with increasing rate of N as well as USG and PU, but ascorbic acid content was slightly decreased with increasing rate of USG and PU. The maximum compactness coefficient (18.61) was found from the treatment USG-N180 that was followed by USG-N160 (18.24) and the highest β-carotene content (0.401 mg/100gFW) was found from USG-N160 followed by PU-N180 (0.40 mg/100gFW). Similarly the highest chlorophyll-a content (0.818 mg/100gFW) was found from USG-N180 followed by USG-N160 (0.814 mg/100gFW) and the highest chlorophyll-b content (1.141mg/100g FW) was recorded from USG-N180. The higher nutrient uptake and N uptake efficiency (108.531%) was obtained from USG treated plots over that of the PU. But N uptake efficiency was decreased with increasing rates of N fertilizer. But post harvest soil nitrogen status did not show any systematic trend although it was found higher in USG over PU. Similarly no remarkable changes were observed in post harvest soil P, K, S and B status for the crop. However, USG @ 160 kg N ha-1 (USG-N160) followed by USG-N140 and PU @ 180 kg N ha-1 (PU-N180) with other recommended doses of fertilizer could be suggested as USG and PU based fertilizer recommendation for a good quality broccoli production in terms of yield and quality in Silty Clay Loam Soil of Madhupur Tract.The Agriculturists 2017; 15(2) 24-39